2021
DOI: 10.7150/ijbs.62858
|View full text |Cite
|
Sign up to set email alerts
|

miR-139/PDE2A-Notch1 feedback circuit represses stemness of gliomas by inhibiting Wnt/β-catenin signaling

Abstract: Rationale:The malignant phenotypes of glioblastomas (GBMs) are primarily attributed to glioma stem cells (GSCs). Our previous study and other reports have suggested that both miR-139 and its host gene PDE2A are putative antitumor genes in various cancers. The aim of this study was to investigate the roles and mechanisms of miR-139/PDE2A in GSC modulation. Methods: Clinical samples were used to determine miR-139/PDE2A expression. Patient-derived glioma stem-like cells (PD-GSCs) were stimulated for immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…He et al concluded that miR-210-3p can inhibit glioma growth, migration, and proliferation by targeting the iron–sulfur cluster assembly protein (Iscu) gene in mouse models [ 83 ]. Another group suggested that overexpression of miR-139 exercises a tumor suppressive effect by inhibiting the stemness GSCs [ 84 ]. The miR-146a suppresses gliomas, whereas the knockdown of miR-146a by miR sponge upregulates Notch1 and promotes tumorigenesis of malignant astrocytes which induce the miR-146a as a negative-feedback mechanism to restrict tumor growth by suppressing Notch1 [ 85 ].…”
Section: Microrna-based Therapeutics Against Glioblastomamentioning
confidence: 99%
“…He et al concluded that miR-210-3p can inhibit glioma growth, migration, and proliferation by targeting the iron–sulfur cluster assembly protein (Iscu) gene in mouse models [ 83 ]. Another group suggested that overexpression of miR-139 exercises a tumor suppressive effect by inhibiting the stemness GSCs [ 84 ]. The miR-146a suppresses gliomas, whereas the knockdown of miR-146a by miR sponge upregulates Notch1 and promotes tumorigenesis of malignant astrocytes which induce the miR-146a as a negative-feedback mechanism to restrict tumor growth by suppressing Notch1 [ 85 ].…”
Section: Microrna-based Therapeutics Against Glioblastomamentioning
confidence: 99%
“…Multiple well-known oncogenes silence the expression of MIR139 in cancer. For instance, NOTCH1 signaling suppresses MIR139 expression via the transcriptional repressor HES1, which binds to the E-box site at position +644 bp in the PDE2A gene in glioma cells ( Figure 2 B) [ 67 ]. In this study, the authors show that miR-139 modulates stemness by inhibiting Wnt/β-catenin signaling, which is a hallmark of cancer [ 67 ].…”
Section: Mir139 Expression Is Repressed In Various Types Of ...mentioning
confidence: 99%
“…For instance, NOTCH1 signaling suppresses MIR139 expression via the transcriptional repressor HES1, which binds to the E-box site at position +644 bp in the PDE2A gene in glioma cells ( Figure 2 B) [ 67 ]. In this study, the authors show that miR-139 modulates stemness by inhibiting Wnt/β-catenin signaling, which is a hallmark of cancer [ 67 ]. As NOTCH1 is a direct target of miR-139 (discussed below), this creates a feedback mechanism that fine-tunes NOTCH1 signaling ( Figure 2 B).…”
Section: Mir139 Expression Is Repressed In Various Types Of ...mentioning
confidence: 99%
“… 345 miR-139 miRNA inhibitory functions on GSC stemness and tumorigenesis inhibiting Wnt/β-catenin signalling Li et al. 202 miR-27a-5p miRNA enhanced the sensitivity of glioma stem cells to radiotherapy shFOSL1-inhibited miR-27a-5p expression Li et al. 346 miR-944 miRNA reduces glioma growth and angiogenesis inhibiting AKT/ERK signalling Jiang et al.…”
Section: Introductionmentioning
confidence: 99%